Cover Image, Volume 138, Issue 42. Issue 42 (2nd August 2021) - Risangud, Nuttapol; Jiraborvornpongsa, Noppakhate; Pasee, Supasin; Kaewkong, Pakkanun; Kunkit, Nootcharee; Sungkhaphan, Piyarat; Janvikul, Wanida
Abstract : The cover designed by Wanida Janvikul and co‐authors displays an SEM micrograph of a digital light processing (DLP)‐printed porous scaffold consisted of poly(caprolactone‐co‐glycidyl methacrylate). The copolymer was synthesized via sequential ring‐opening polymerization of ε‐caprolactone and glycidyl methacrylate, which bypassed the usages of substantial chemicals and complicated purification steps. This versatile neat synthetic route explicitly opens up a new method to prepare biodegradable light‐assisted 3D printing materials from other biodegradable cyclic ester monomers. DOI: 10.1002/app.51391